2010
DOI: 10.1182/blood-2009-10-249177
|View full text |Cite
|
Sign up to set email alerts
|

Cellular source and molecular form of TNF specify its distinct functions in organization of secondary lymphoid organs

Abstract: IntroductionSecondary lymphoid organs provide an important microenvironment for the initiation and development of efficient immune responses. Their highly sophisticated structure allows migration and interactions between antigen-presenting cells, T and B lymphocytes, as well as follicular dendritic cells (FDCs) and other stromal cells. The cooperation of the lymphoid cells within secondary lymphoid organs dramatically increases the probability of interactions of rare B, T, and antigen-presenting cells that res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 50 publications
2
80
0
1
Order By: Relevance
“…In mice, the deficiency for TNF or TNF receptors interferes with the formation of B cell follicles, follicular DC networks, and germinal centers in secondary lymphoid organs (13,14). We therefore performed anti-TNF antibody studies, which showed that neutralization of TNF during the effector phase of LZT but not during the induction phase of LZT significantly inhibited the development of LZT (Supplemental Figure 3, A and B).…”
Section: Tnf and P75 Are Critical For The Effector Phase Of Lzt But mentioning
confidence: 99%
“…In mice, the deficiency for TNF or TNF receptors interferes with the formation of B cell follicles, follicular DC networks, and germinal centers in secondary lymphoid organs (13,14). We therefore performed anti-TNF antibody studies, which showed that neutralization of TNF during the effector phase of LZT but not during the induction phase of LZT significantly inhibited the development of LZT (Supplemental Figure 3, A and B).…”
Section: Tnf and P75 Are Critical For The Effector Phase Of Lzt But mentioning
confidence: 99%
“…[141][142][143] Importantly, B cellderived TNFa is critical for the formation of FDC networks, GC and B cell follicles in the spleen, while TNFa from B and T cells synergizes for GC and FDC networks in LN, which is critical for the generation of local immune responses. 144,145 Moreover, maintenance of long-lived PC in BM is thought to require a specialized niche that mediates their survival at least partially through TNFa. 146 Lastly, full maturation of ILF requires TNFRI, 21 and B cell-derived TNFa was also shown to regulate GC in PP.…”
mentioning
confidence: 99%
“…Our findings link protective and pathogenic effects of TNF in CNS autoimmunity to specific cellular sources and suggest that the balance between the effects of TNF in the target organ and peripheral lymphoid tissues is crucial for the final outcome of the disease. -TNF KO; TNF flox/flox CD19-Cre), as well as the TNF KO mice, used in this study were described elsewhere (14,17). Concomitant ablation of TNF in both T cells and myeloid cells (MT-TNF KO; TNF flox/flox MlysCre CD4-Cre) was achieved by crossing M-TNF KO and T-TNF KO mice.…”
mentioning
confidence: 99%